Reliability of spatial rod metal structures of high level of responsibility - V. F. Mushchanov; A. N. Orzhekhovskiy; A. V. Mushchanov; M. N. Tseplyaev (Vestnik MGSU)
Introduction. Spatial rod metal structures of high level of responsibility are the most frequently used as structural systems for covering large spans of buildings and structures. However, progressive destruction can actively develop in these systems under unfavorable combination of factors. The aim of the research is to develop scientific justification of new approaches to the design of optimal spatial metal structures resistant to the development of progressive collapse of high level of responsibility with guaranteed levels of reliability of key and secondary elements.Materials and methods. The main research methods in the work are methods of structural mechanics in the form of the finite element method, methods of similarity theory, and methods of the theory of reliability of building structures.Results. As a result of the research work for the considered structures, a 2-stage algorithm for assessing reliability was developed, which differs from the previously developed ones by the possibility of assessing the development of progressive collapse. The results of its testing for frame-cantilever structures of coverings over stadium stands are presented in the form of established values of reliability indicators for a set of key elements. A similar assessment was made for the implemented reconstruction project of the long-span covering of the “Ilyichevets” sports complex (Mariupol).Conclusions. To assess the reliability of the studied structures, taking into account the tendency to the development of progressive collapse, a universal algorithm is proposed and tested in practical design, the main components of which are computer modelling of the process of successive failures of structural elements, and the establishment of failure probability values for the selected set of key elements. The studies carried out on the basis of its algorithm made it possible to identify a set of key elements of the cantilever part for the frame-cantilever coverings above the stadium stands, the failure of which initiates the beginning of an avalanche-like collapse, and to set limits for them to change the values of safety characteristics and survivability reserve. Additionally, the main provisions of the developed approach were experimentally tested during the development and implementation of the project of reinforcement of large-span bearing structures of the covering of the “Ilyichevets” sports complex (Mariupol).